Synectics Model: An Offer to develop Students’ Creativity Through Science Learning - Tomo Djudin (JETL (Journal of Education, Teaching and Learning), 2017)
Creativity plays an important role in everyday life. The main basis for the emergence of creativity is the use of existing knowledge imaginatively (creatively) to produce a new, unusual, and useful product. Interpretation of a problem in a new and different way (restructuring) and incubation is an additional basis for the emergence of creativity. The Synectics model is designed based on two main strategies: (1) Designing something (problem, idea, product) that has been previously known to be something new; and (2) Creating something new becomes more known and meaningful.